PENERAPAN MEDIA KARTU SOAL UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN REAKSI OKSIDASI REDUKSI DI KELAS X SMA NEGERI 10 PEKANBARU - Muhammad Yani; Erviyenni '; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to improve student’s achievement on reduction oxidation reactions subject through an application of question card media in class X SMAN 10 Pekanbaru. The conducted research type is quasi experimental study using Design Randomized Control Group Pretest-Posttest. Sample of the research consisted of two classes, a class X1 as an experimental class (implemented question card media) and class X2 as the control class (without question card media). T-test was used as analysis technique. Based on the data analysis obtained t>ttable ie 2.21>1.66,meaning that the application of question card media can improve the student achievement on the subject reduction oxidation reaction in class X SMAN 10 Pekanbaru. The category improvement of student achievement in experiment class was medium category with a score gain normalized is 0,50.KeyWords: Question Card Media, learning Achievement, Reduction Oxidation Reaction